Outcomes of the Round Table "Current Problems in the Organization and Implementation of Continuing Professional Education in the System of Forensic Science Organizations of the Russian Ministry of Justice" - M. V. Toropova (Теория и практика судебной экспертизы, 2017)
The paper presents the outcomes of the Round Table "Current Problems in the Organization and Implementation of Continuing Professional Education in the System of Forensic Science Organizations of the Russian Ministry of Justice" hosted December 7th, 2016 by the Ministry of Justice in Moscow.